2001
DOI: 10.1149/1.1414942
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Silver Thin Films Using Low Power Chlorine Plasmas

Abstract: Modification of silver thin films to create Ag/AgCl thin film electrodes, using a plasma process, was investigated and the efficiency of the plasma technique was assessed. X-ray photoelectron spectroscopy measurements revealed the presence of AgCl within the thin film after plasma treatment. The observed binding energy peak shifts corroborated with values found in literature. Auger spectroscopy depth analysis showed that, under low input power conditions, the plasma process is controlled by the chlorine flow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The XPS spectrum revealed also the presence of C as organic contaminant coming from the soil as for chloride ions [4,8,13] . The overall results allow to establish that the chloride compound has a chemical structure similar to AgCl [12][13][14] . The second case study is a brittle Carthaginian bracelet whose micro-chemical composition and whose micro-structure was investigated by means of the combined use of the above-mentioned analytical techniques.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The XPS spectrum revealed also the presence of C as organic contaminant coming from the soil as for chloride ions [4,8,13] . The overall results allow to establish that the chloride compound has a chemical structure similar to AgCl [12][13][14] . The second case study is a brittle Carthaginian bracelet whose micro-chemical composition and whose micro-structure was investigated by means of the combined use of the above-mentioned analytical techniques.…”
Section: Resultsmentioning
confidence: 76%
“…9: the spectrum shows that the dominant peaks are Ag 3p, Ag 3 d, C 1 s and O as well as Cl 2p along with Auger peaks Ag MNN. The BE of the photoemission signals was measured and compared to the values found in literature [12] . The measured BE values are the following: Ag 3 d 5/2 368.1 eV, Ag MNN 1129.7 eV, Cl 2p 3/2 198.4 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The diffractogram of Fig. (2), taken in a darker area, reveals the additional presence of copper sulphides, such as Cu 9 S 5 (digenite), that develop if the reactive sulphide anions are present …”
Section: Resultsmentioning
confidence: 99%
“…3. 11 Matsunaga et al 17 have shown that several types of nonstoichiometric structure, Ag x Cl y , can exist due to the possible presence of interstitial Ag as well as cation vacancies, 18 leading to structural flexibility and higher conductivity. This decrease in the impedance locus may also be a consequence of a larger active surface area, as it affects the pseudocapacitance component.…”
Section: Discussionmentioning
confidence: 99%